Unexplored Syria visits to the Libanus, the Tulúl El Safá, the Anti-Libanus, the Northern Libanus, and the 'Aláh/ by Richard F. Burton and Charles F. Tyrwhitt Drake - Burton, Richard, Sir, 1821-1890 (Tinsley Brothers, 1872)
Penzer 85.